Desempeño productivo de la progenie de un cruzamiento entre Limangus y Angus. Comunicación - Lopez Valiente, Sebastian; Perazzo, V.; Rodriguez, Alejandro Martin; Ferrario, J.; Montes, Andrés Domingo; Vara Solana, Gema; Maresca, Sebastian (Asociación Argentina de Producción Animal (AAPA), 2024)
Póster